Inhomogeneous Perforated Reflect-Array Antennas - Moeini-Fard, Mojtaba; Khalaj-Amirhosseini, Mohammad (Scientific Research Publishing, 2011)
A new reflect-array antenna structure is proposed. This structure utilizes a perforated substrate as a reflecting surface with the lattice of different holes. The effective electric permittivity of the dielectric substrate is altered by drilling holes with different diameter and spacing, which provide an in-homogeneous dielectric layer. This in-homogeneous dielectric layer can be controlled by these holes to collimate the reflected waves in the special direction. Absence of resonator elements in this structure will reduce the dielectric and conductor losses, which are the main losses in reflect-array antennas at resonance frequency. In addition, a simple method based on an equivalent circuit model is introduced for designing and analyzing this kind of antennas. Using this method, the suitable values of the diameter and spacing of the holes at each point on the reflecting surface are obtained. Some proposed antennas are designed at millimeter wave frequency and simulated by full-wave analyzer; CST Microwave Studio software to verify theoretical results.
Keywords: Perforated Substrate; Reflect-Array Antenna